호남평야지 재배시기별 조생종 벼 품종의 품질 및 호화점도 특성 분석 - 박현수(Hyun-Su Park), 백만기(Man-Kee Baek), 이창민(Chang-Min Lee), 김석만(Suk-Man Kim), 서정필(Jung-Pil Suh), 정오영(O-Young Jeong), 조영찬(Young-Chan Cho) (Korean journal of breeding, 2021)
Early maturing rice is widely utilized to diversify cropping systems in the Honam Plain, Korea. It is based on the principle ofa short growth duration. There is concern regarding quality deterioration of early maturing rice owing to the high temperature during theripening stage as compared to that for mid and mid-late maturing rice. This study was conducted to analyze six pasting property-related andeight quality traits of six early maturing rice varieties (Jopyeong, Odae, Unkwang, Haedamssal, Jinkwang, and Haedeul) on early, ordinary,and late cultivations, and to interpret the relationships between genotypes and environments. As the cultivation time increased, the ratio ofhead rice (HR) and glossiness of cooked rice (Toyo value, TY) increased. The cumulative mean temperature of the ripening stage showeda strong negative correlation with HR and TY at all cultivation times. Pasting temperature, peak viscosity (PV), trough viscosity, final viscosity,and breakdown (BD) decreased, whereas setback (SB) increased as the cultivation time was delayed. Pasting properties were affected moreby climate conditions in the ripening stage than during the growth stage. Additive main effects and multiplicative interaction analysis revealedthat pasting property-related and quality traits were affected more by environment than genotype. Jinkwang and Haedamssal in early and ordinarycultivation and Jinkwang and Haedeul in late cultivation exhibited higher HR and TY and a lower protein content. They also showed higherPV and BD and lower SB, which are characteristics of good eating quality japonica rice. Jinkwang, Haedamssal, and Haedeul are premium-quality,early maturing rice varieties that were recently developed. The cultivation of these varieties could improve the grain quality of early maturingrice at high temperatures during the ripening stage in the Honam Plain. KCI Citation Count: 4